Tipo de tierra y su resistencia a la compresión del adobe con cáscara de arroz en Zungarococha. Loreto, 2020 - Tello Treneman, Diego Benjamin (2021)
The objective of this research was to evaluate the compressive strength of artisanal adobe with two types of soils, one clay and the other sandy clay with 30% rice husk. The land used for the elaboration of the units was extracted from the community of Zungarococha, from the Faculty of Agronomy, of the National University of the Peruvian Amazon. The work was carried out in the soil laboratory of the Faculty of Agronomy. The results show that the highest compression value (p < 0.01) was the adobe based on clay soil with an average stress of 28.62 kg/cm2, a value higher than the average compressive strength of the sandy clay adobe, which was of 11.21 kg/cm2. The data recorded for the effects of moisture loss, correspond to the drying of the adobe at room temperature from the first day, the highest value of weight loss (p < 0.01), was the clay-based adobe with an average of 1.55 kg , value greater than the average weight loss of the sandy clay adobe, which was 1.27 kg. time when the weight stabilizes and shows no weight loss due to moisture content.